Evaluation of partial wound closure in perforated appendicitis - Jaafar Al-Sa’adi, Muhammed H.; Zamil, Ali Laibi (International Surgery Journal, 2019)
Background: Perforated appendicitis is a serious complication of acute appendicitis that usually occurs due to over delay in presentation, diagnosis, and surgical treatment. Wound infection is one of the important sequelae of perforated appendicitis. Method of the wound closure in perforated appendicitis is a critical factor that affects the incidence of wound infection and there is continuing controversy about the best method. Methods: 362 patients with a diagnosis of acute appendicitis were enrolled in a prospective randomized study that extended over three years. The intraoperative gross pathological state of the appendix was recorded as either negative or uncomplicated or perforated appendicitis. The relationship between the wound infection with each one of the three methods of wound closure (primary closure, open wound with delayed primary closure and partial wound closure) had been reported. The hospital stays were recorded for each method. Results: 18.78% of appendectomy was appendicitis negative, 62.98% uncomplicated appendicitis and 18.23% with perforated appendicitis. In the perforated appendicitis cases, Primary wound closure was used in 36.36%, open method and delay primary closure in 18.18% and partial wound closure in 45.45%. The wound infection rates were 37.5%, 16.66% and 13.33% in primary wound closure, open wound with delayed primary closure and partial wound closure respectively. Length of hospital stays were 7 days, 8 days and 4 days respectively. Conclusions: partial wound closure is superior to other methods of wound closure, which are primary wound closure and open wound with delayed primary wound closure.